Exploring Freudian Defense Mechanism Theory in the Portrayal of Paul Atreides in the Movie 'Dune’ - Mufidah Kutfiyah Sari; Rani Roanliq Lamahayu; Firsta Marchania Rachman; Aulia Nurul` Izza; Ega Citta Salsabilla; Rina Saraswati; Rizal Octofianto Datau (ARIMA : Jurnal Sosial Dan Humaniora, 2023)
This study explores the complex character of Paul Atreides in the movie “Dune” (2021), using psychoanalysis theory to uncover the hidden behaviors that determine Paul's psyche. While many analyses of "Dune" exist, there is a gap in that existing research focuses on broader themes, and this study tries to fill that gap by providing an in-depth exploration of Paul's psyche. This study aims to point out and interpret Paul's defense mechanisms in response to the chaotic events on Arrakis by analyzing the film's narrative and character development. This analysis uses qualitative research with Freud's psychoanalytical frameworks through Defense Mechanism Theory to examine the main character's psyche, motivations, and development in the movie "Dune." The methodology analyzes the character's actions, interactions, and personal journeys within the narrative, shedding light on their role in the film's narrative. The results show four types of Defense Mechanisms found in Paul Atreides as a protagonist in the movie "Dune": repression, denial, projection, and sublimation. This study concludes that the psyche, motivations, and character development of the main character, Paul Atreides, are evoked by the relationships and situations present in the film's narrative using a psychoanalytic framework.